Evaluation of The Suitability of Urban Parks Based on The Characteristic of The Elderly’s Needs in Surabaya - Anindita Ramadhani; Endang Titi Sunarti Darjosanjoto; Murni Rachmawati (Institut Teknologi Sepuluh Nopember, 2015)
The number of elderly people in Surabaya City is growing fast, with the largest population in Development Unit (UP) Tunjungan. It resulted to the needs of elderly facilities, such as parks. The elderly have certain characteristics, so the designing of elderly park need a specific approach. Therefore, the research’s objective is to evaluate urban parks in UP Tunjungan that suitable for characteristic of the elderly’s need. The research’s methods is qualitative descriptive. The evaluation of eight parks in UP Tunjungan based on general criteria of elderly park through character appraisal analysis. The result is to find out the most suitable park to be designed as Elderly Park that meets 7 out of 10 sub criteria of an elderly park.